Husbandry, nutrition and productivity of goats and sheep in tropical Africa - Wilson, R.T. (International Livestock Centre for Africa, 1982)
Examines sheep and goat husbandry including breed types and ownership; nutrition and productivity. Tabulates their contribution to liveweight biomass, meat production, and registered slaughtering. Shows some measured production parameters for African goats and sheep in semi-arid areas. Looks at the potential for improved production.